தற்காலப் பயன்பாட்டில் வினையெச்சச் சொற்கள் / Adjectives in Modern Use - கோ. கோகிலா / G. Kokila (International Journal of Tamil Language and Literary Studies)
Tamil people's knowledge has been revealed through ancient palm-leaf manuscripts. Among the grammar and literary texts available in Tamil, grammar has been structured into five categories: ezhuthu (letters), sol (words), porul (meaning), yaappu (prosody), and ani (figure of speech). One of the ancient grammatical texts, Tholkappiyam, consisting of 27 chapters (Iyals) holds a distinctive position regarding words (sol). In the sixth chapter under the Sollathikaram (the section on words), called Vinaiyiyal (the chapter on verbs), the grammar of verbs specifies that they function according to time rather than case distinctions. It explains that verbs accommodate three temporal aspects (past, present, and future) and discusses their applications. In this regard, Tamil verbs serve as a bridge to meaning and contribute to sentence formation. Among the four types of words, verbs are indispensable for conveying meaning, and their role as the foundation of sentence construction is emphasized by grammatical commentators. In contemporary usage, influenced by migration and the appeal of reading, simpler styles are adopted. Verbs that adapt only to temporal changes in Tamil are classified into two categories. Verbs are key components in a sentence to express an action or state. They vary based on aspects such as tense, verb focus, verb types, and distinctions. By categorizing verbs based on their morphological and phonological behavior is useful for understanding their transformations and functions. Among verbs that signify time without case distinctions, verbal roots (vinaiyeccam) are an important subset. Tamil grammarians have categorized over ten verbal roots. However, modern literary usage shows the inclusion of many more such words and they are highlighted in this research.